Kyle Mandeville: capstone - Mandeville, Kyle, artist (Colorado State University. Libraries, 2013)
The artist's statement: In my art I enjoy taking objects that have been mass-produced or extensively used and transforming the quality, style and personality of that object. Through the thoughtful combination of materials and techniques I create visual complexity that accentuates the role of each piece. I enjoy working in series because of the continuity between one piece and another. My current work focuses on paying homage to my college career using aspects of my experiences and focusing on elements of my future. To express the turning of a new page in my life I use feathers and the image of a phoenix to express a new birth, while the shot glasses and enameled Colorado State symbols represent my time in college. Each element is positioned symmetrically to provide visual balance and make for a pleasant user experience.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.